Investigating in novel CdZnSe/CdSe/CdZnSe quantum well with 97% PLQY - Zou, Shi-Bing; Fan, Hao; Yang, Hao; Feng, Lu-Xin; Duan, Jun-Hong; Liu, Wei-Qing; Wu, Hua-Ming (Modern physics letters. B, Condensed matter physics, statistical physics, applied physics, 2020)
Thick-shell not only provides colloidal quantum dots (QDs) stability and workability, but also plays a significant role in passivation of QDs surface defects and change of electron transport characteristics of QDs. Here, the dedicated design and synthesis of high luminescence CdZnSe/CdSe/CdZnSe quantum wells are reported by precisely controlled shell growth. By tuning the thicknesses of the CdSe and CdZnSe layers, photoluminescence quantum yields (PLQY) can be attained a maximum of 97% as the CdSe shell thickness is 4 monolayers and the CdZnSe shell thickness is 10 monolayers. These gradient thick shell CdZnSe/CdSe/CdZnSe quantum wells confirm the suppression of surface trap-state emission in gradient core/shell structures. Superior optical properties render CdZnSe/CdSe/CdZnSe quantum wells suitable for use in solid-state lightings.